(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
Cultivation of algae Aldrovanda vesiculosa L makes it possible to provide agriculture with organically saturated and purified water, as well as effective organic fertilizer, and the purification of reservoirs with the help of this plant is one of the urgent tasks of our time. environmentally friendly food products are highlighted, which are one of them